Agricultura urbana na cidade de Teresina: hortas comunitárias - políticas públicas ou segurança alimentar? - Teixeira, Marcos Antonio de Castro Marques [UNESP] (2011)
The urban gardens are part of the landscape of the city of Teresina, state of Piauí, Brazil, since 1996, when they were incorporated to changes in the social, environmental structure and in the quality of life. At the same time, they seek to bring together a dimension of development with social justice and sustainability. Throughout this study, we surveyed two distinct areas of the city of Teresina, state of Piauí, Brazil: Santa Maria da Codipi, located in the northern part of Teresina, and Dirceu Arcoverde in the south-east, whose objective was to prove the economic viability of urban gardens for gardeners in the increase income, and provide opportunities for integration with the green of the city with a predominantly rural landscape mode. In both areas, the problems arising ranging from petty theft, which contradict the goal of the program, the low level of education, to the lack of technical assistance, which reflects not daring to invest in new crops by gardeners. In addition, the use of pesticides disadvantage in competitive advantage over traditional cultures. The urban gardens in the two areas, despite being in harmony with the spaces where they are located, do not reflect, for those who work at them, an income security. However, without them, there is a void not only in physical appearance but also in the isolation of neighborhoods in relation to the evolution of cities